2017
DOI: 10.1016/j.applthermaleng.2017.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inclination on pressure drop and flow regimes in large flattened-tube steam condensers

Abstract: This thesis presents an experimental study of the inclination effect on pressure drop and flow regime during condensation of steam in a large flattened tube used in air-cooled condensers (ACC) for power plants. Steam Because of the creation of the visualization window, the tube width was less than that used in industry, and thus a model that accounts for the differences in tube geometry between the full and test tube was developed and used to convert experimental pressure drop results to the full-sized tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The increase in the inclination (for slightly inclined tubes) improved the two-phase heat transfer with the rise of the waves creating larger and frequent splashes for the wavy flow, while for the slug flow, the two-phase heat transfer improved with more intensive mixing effects depending on the change in the balance between the buoyant force and the inertia force [13]. Under low mass flux conditions and for large flattened steam condensing tubes, increasing the inclination angle caused a decrease in pressure drop; and the flow visualisation outputs indicated that large void fraction and low vapour velocity occurred at high inclination angles [14]. For U-bend tubes, stratified and stratified-wavy flow regimes appeared at low-vapour qualities, annular flow was observed at high-vapour qualities where the effects of gravitational and centrifugal forces could be neglected.…”
Section: Literature Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The increase in the inclination (for slightly inclined tubes) improved the two-phase heat transfer with the rise of the waves creating larger and frequent splashes for the wavy flow, while for the slug flow, the two-phase heat transfer improved with more intensive mixing effects depending on the change in the balance between the buoyant force and the inertia force [13]. Under low mass flux conditions and for large flattened steam condensing tubes, increasing the inclination angle caused a decrease in pressure drop; and the flow visualisation outputs indicated that large void fraction and low vapour velocity occurred at high inclination angles [14]. For U-bend tubes, stratified and stratified-wavy flow regimes appeared at low-vapour qualities, annular flow was observed at high-vapour qualities where the effects of gravitational and centrifugal forces could be neglected.…”
Section: Literature Studiesmentioning
confidence: 98%
“…Kang et al [14] experimentally studied the inclination effect on the flow regime of the condensation of steam in a large flattened tube. An air-cooled condensation process was carried out for power plants with mass flux of about 7 kg m 2 s -1 , length of 10.7 m and the tube orientation varied from horizontal up to 70°.…”
Section: Literature Studiesmentioning
confidence: 99%
“…The condensation process is one of the major causes of losses in power plants. During the past few years, significant efforts have been made to improve condensation efficiency by focusing on novel ideas such as using enhanced surfaces (Zhao et al, 2016), imposing inclination angles (Würfel et al, 2003;Meyer et al, 2014;Adelaja et al, 2016;Noori Rahim Abadi et al, 2018b,c), developing new cycles or improving the condensation process in the thermal cycles (Matsuda, 2014;Zhang et al, 2016h;Bao et al, 2017b), and proposing new cross-sectional geometries (Chiou et al, 1994;Chen et al, 2014;Kang et al, 2017;Mahvi et al, 2018).…”
Section: Combined Cyclesmentioning
confidence: 99%
“…A complete description of the experimental procedure and void fraction results is also presented in Kang et al (2017) so the details are not presented here. Experiment results for capacity, overall HTC, and condensate river depth are presented here for comparison to the model.…”
Section: Condenser Tube and Facilitymentioning
confidence: 99%